Iranian Freaks: Embodying the Violence of the Times in Contemporary Iranian Fiction - Duvigneau, Julie (Oriente moderno, 2024)
Malformed, mutilated, dismembered, blinded, paralyzed, characters in contemporary Iranian literature are subjected to brutal abuse. This article aims to show that these torments, through the work of seven authors: Ṣādeq Hedāyat, Hušang Golširi, Bahrām Ṣādeqi, Reżā Barāheni, Qāżi Rabiḥāvi, Esmāʿil Faṣiḥ and Nasim Marʿ aši, all over whom the shadow of Hedāyat looms, are the incarnation of historical violence in the flesh of contemporary Iranian literature. I argue that the metamorphoses of violence that run through Iranian literature in the 20th and early 21st centuries, beyond the differences in meaning it may have, highlight a poetics of cruelty that is particularly evident in the texts of these authors.